Finite Element Analysis of Seepage and Exit Gradient underneath a Hydraulic Structure (Weir) by Using Geo-Slope (SEEP/W) Software - Arshad, Imran (PSM Biological Research, 2022)
In this study, a weir section of Runpur bund located in Sindh province of Pakistan was examined. A 2-dimensional model was generated using finite element based software Geo-Slope, SEEP/W. The model was run for two different cases i.e. (i) original design, and (ii) without sheet piles respectively. The study aims to calculate the amount of seepage (q) underneath the weir foundation and to calculate exit gradient (GE) for five different hydraulic heads i.e. EL 25m, EL 25.7m, EL 26.7m, EL 27.7m, and EL 28.7m respectively. The seepage results showed that at original design a normal behavior of the weir for various hydraulic heads was observed. The overall maximum resultant seepage quantity (q) 7.21x10-6 m3/sec/m and exit gradient (GE) 0.57 for the hydraulic head EL 28.7m respectively. However, abnormal behavior of the weir without sheet piles was observed with maximum resultant seepage quantity (q) 78.20x10-6 m3/sec/m and exit gradient (GE) 2.27 for the hydraulic head EL 28.7m respectively. It has been found that without the provision sheet piles the internal pore water pressure underneath the weir foundation was increased and the overall seepage and exit gradient will increase up to 90.78% and 74.88% respectively. Therefore, the weir is not safe without the installation of sheet piles.